2021
DOI: 10.1155/2021/6626313
|View full text |Cite
|
Sign up to set email alerts
|

Use of Different Natural Products to Control Growth of Titanium Oxide Nanoparticles in Green Solvent Emulsion, Characterization, and Their Photocatalytic Application

Abstract: Water, one of the crucial and the pillar resources to every living thing, could be polluted day to day by different causes such as expansion in industrialization, rapid increment in population size, the threat of climate, and growth of urbanization. The existence of a number of organic dyes, detergents, and pesticides from industrial effluents could lead to severe diseases and even to the death of human beings. Currently, remediation of those hazardous organic contaminants using semiconductor metal oxide catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 81 publications
4
8
0
Order By: Relevance
“…It demonstrates that particles were tightly scattered over a small dispersion range [140]. Nanoparticles with a smooth surface morphology were used [137]. Cerium oxide Antioxidant, low reduction potential [129] the properties of the nanomaterials that are being formed and learn further about them.…”
Section: 43mentioning
confidence: 99%
See 2 more Smart Citations
“…It demonstrates that particles were tightly scattered over a small dispersion range [140]. Nanoparticles with a smooth surface morphology were used [137]. Cerium oxide Antioxidant, low reduction potential [129] the properties of the nanomaterials that are being formed and learn further about them.…”
Section: 43mentioning
confidence: 99%
“…Roopa et al [ 136 ] reported on similar research as well. As per Vijayalakshmi and Rajendran, the spectra exhibit a spectral range of 200–1200 nm, with a peak at 354 nm wavelength and intensity of 0.86, indicating considerable UV absorbance [ 137 ].…”
Section: Characterization Of Bioinorganic Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top-down approach starts with size reduction from the bulk material to the nanosized with physical methods such as ball milling and laser ablation ( 6 ), while the bottom-up approach needs a reducing agent to decrease the size of the particle. Chemical (for example, sodium hydroxide and potassium hydroxide) and biological [biomolecules from bacteria ( 6 ), fungi ( 7 ), yeast ( 8 ), virus ( 9 ), and plant extracts ( 10 )] reducing agents can work perfectly for controlling the size of metals and metal oxides. Biomolecules are preferred due to their safety and biocompatibility with DNA, proteins, enzymes, polyphenols, flavonoids, and sugars ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quite a few reports are available on the green synthesis of TiO 2 nanoparticles using various plant extracts like Nyctanthes arbor-tristis, Solanum trilobatum, Annona squamosa, Catharanthus roseus, Jatropha curcas, Cucurbita pepo, Eclipta prostrata, C. gigantea, and Ocimum basilicum (Ocimum tenuiflorum) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) . C. gigantea is a well-known medicinal plant belongs to the Asclepiadaceous family, this plant is widely used as a scent through which it netted its title Queen (basileus) of aromatic herbs (29) .…”
Section: Introductionmentioning
confidence: 99%